ER stress-driven unfolded protein response fuels aging-related tumor aggressiveness in gliomas - Shao, Xiaodong; Guo, Shaolei; Yang, Jia; Dai, Junjie; Cao, Kaihua; Cai, Xia; Song, Tianshi; Yao, Shun; Raza, Umar; Chen, Kun (Frontiers in Molecular Biosciences, 2025)
BackgroundGliomas are the most prevalent and aggressive primary brain tumors. Aging significantly influences glioma incidence and progression, yet the molecular mechanisms linking aging-related pathways to tumor aggressiveness remain poorly understood. Here, we aimed to decipher aging-related molecular mechanisms regulating tumor aggressiveness in gliomas.MethodsWe performed comprehensive aging-targeted transcriptomic analyses using TCGA-glioma patient dataset. Differential gene and protein expression, functional annotation and pathway enrichment, gene set enrichment, network construction, CRSISPR-based functional dependency, transcription factor prediction, correlation, clinical association and survival analyses were conducted to identify, develop and validate endoplasmic reticulum (ER) stress-driven unfolded protein response (UPR) as key aging-related molecular mechanism driving tumor aggressiveness in gliomas. Notably, we validated our findings in multiple independent GEO datasets.ResultsWe identified ER stress and UPR as key aging-related mechanism behind tumor aggressiveness in gliomas, and developed a six gene “ER Stress and UPR-driven Aging-related Tumor Aggressiveness in Glioma” (ESURATAG) gene signature, comprising DERL2, RPN2, SEC13, SEC61A1, SEC61B, and STT3A. Notably, glioma cell proliferation critically depends on ESURATAG-GS, which is preferentially regulated by MYC and is associated with disease and cell cycle progression, inflammation, and poor clinical outcomes in glioma patients, simultaneously aligning with aging and tumor aggressiveness signatures. Validated in multiple GEO datasets, high ESURATAG expression is linked to disease onset, advanced disease state, and reduced overall and progression-free survival in glioma patients as well as in patients with major subtypes of gliomas, including oligodendrogliomas, astrocytomas and gliobalstomas.DiscussionESURATAG-GS serves as a critical MYC-regulated adaptive mechanism that fuels aging-related tumor aggressiveness via ER stress-driven UPR in gliomas, presenting novel prognostic markers and therapeutic targets for elderly glioma patients.